Does Family History of Obesity, Cardiovascular, and Metabolic Diseases Influence Onset and Severity of Childhood Obesity? - Corica, Domenico; Aversa, Tommaso; Valenzise, Mariella; Messina, Maria Francesca; Alibrandi, Angela; De Luca, Filippo; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2018)
Objectives To evaluate: 1) the metabolic profile and cardiometabolic risk in overweight/obese children at first assessment, stratifying patients according to severity of overweight and age; 2) to investigate the relationship between family history for obesity and cardiometabolic diseases and severity of childhood obesity . Methods In this cross-sectional, retrospective, observational study, 260 children (139 female), aged between 2.4 and 17.2 years, with overweight and obesity were recruited. Data regarding family history for obesity and cardiometabolic diseases were collected. Each patient underwent clinical and auxological examination and fasting blood sampling for metabolic profile. HOMA-IR, triglyceride-to-HDL-cholesterol-ratio and atherogenic index of plasma were calculated. To evaluate the severity of obesity, children were divided into two groups for BMI SD ≤ 2.5 and BMI SD >2.5. Moreover, study population was analyzed dividing it into three groups based on chronological age of patient (<8, 8-11, >11 years). Results BMI SD was negatively correlated with chronological age (p<0.005) and significantly higher in the group of children <8 years. BMI SD was positively associated with family history for obesity. Patients with more severe obesity (BMI SD>2.5) were younger (p<0.005), mostly pre-pubertal, presented a significantly higher HOMA-IR (p=0.04), and had a significantly higher prevalence of family history for arterial hypertension, type 2 diabetes mellitus and coronary heart disease than the other group. Conclusions 1) Family history of obesity and cardiometabolic diseases are important risk factors for precocious obesity onset in childhood and are related to the severity of obesity. 2) Metabolic profile, especially HOMA-IR, is altered even among the youngest obese children at first evaluation; 3) stratification of obesity severity, using BMI SD, is effective to estimate the cardiometabolic risk of patients.